Coping Strategies of Pregnant Women Who Experience Violence In Asia: Scoping Review - Lukman, Sesaria; Kit, Ayano; Pratiwi, Cesa Septiana (Women, Midwives and Midwifery, 2025)
Background : Partner violence profoundly affects women's physical, mental, sexual, and reproductive health, including adverse consequences for maternal and fetal well-being during pregnancy. Purpose : This scoping review aims to explore current research focusing on coping strategies employed by pregnant women experiencing violence in Asia. Methods : This scoping review employed the Population, Concept, and Context (PCC) framework to investigate coping strategies of pregnant women experiencing violence in Asia. A total of 12 articles meeting inclusion criteria were selected from 536 identified through databases like PubMed, ScienceDirect, EBSCO, Wiley, and grey literature from Research Rabbit. Articles were published between 2018 and 2023 in English. The critical appraisal method using the Joanna Briggs Institute (JBI) study tool guided review selection and characterization. Studies predominantly originated from Asian countries and utilized RCT, cross-sectional, pre-experiment, cohort, and qualitative methods. Results : The review categorized findings into four themes: types of violence, factors influencing violence occurrence, impacts of violence, and coping strategies adopted by pregnant women. Conclusions : Pregnant women primarily employed escape and situation improvement strategies to cope with violence. Recommendations include integrating routine violence screening, psychosocial interventions in ANC services, and violence counseling to enhance accessibility and prevent escalating violence incidents.